Effects and Safety of FGF21 Analogs on Glycemic Parameters, Lipid Profiles, and Adiponectin in Overweight and Obese Adults: A Meta-Analysis of Randomized Controlled Trials - Zizheng Nie; Jiaoyang Xu; Yingying Liu; Qinglong Cao; Xinyi Qiu; Yiping Su; Shufen Han (International Journal of Endocrinology, 2025)
Conclusions: We identified significant favorable effects of FGF21 analogs in improving lipid profiles and elevating circulating ADP levels in overweight and obese adults. Future studies are needed to evaluate the clinical benefits in this area of research.